BISPECIFIC ANTIBODIES ENABLE SYNTHETIC AGONISTIC RECEPTOR T CELL THERAPY IN MELANOMA - Benmebarek, M.; Maerkl, F.; Keyl, J.; Cadilha, B.; Geiger, M.; Karches, C.; Obeck, H.; Schwerdtfeger, M.; Briukhovetska, D.; Jobst, J.; Mueller, Pj; Seifert, M.; et al. (JOURNAL FOR IMMUNOTHERAPY OF CANCER, 2022)
Background Immunotherapies, like immune checkpoint inhibition and tumor infiltrating lymphocytes, have had remarkable success in treating melanoma. However, many patients do still not respond or relapse with therapy-resistant disease. To overcome said limitations, we propose a controlled adoptive cell therapy approach, where T cells are armed with EGFRvIII synthetic agonistic receptors (E3 SAR) that are selectively activated by a cross-linking bispecific antibody (BiAb) specific for both SAR T cell and melanoma-associated antigens. Materials and Methods Murine as well as human SAR constructs were generated and T cells were retrovirally transduced to stably express the SAR constructs. We validated our approach in murine, human and patient-derived cancer models expressing the melanoma-associated target antigens TYRP1 and MCSP. SAR T cells were functionally characterised by proving specific activation and proliferation of SAR T cells, as well as their tumor-directed cytotoxicity, in vitro and in vivo. Results Both on a mRNA and protein level, MCSP and TYRP1 were shown to be differentially expressed in treatment-naive as well as treatment-resistant melanoma patients compared to samples from healthy donors. Crosslinking anti-TYRP1 x anti-E3 and anti-MCSP x anti-E3 BiAb mediated conditional antigen-dependent activation, proliferation of SAR-T cells and lead to tumor cell lysis in all models tested. In vivo, anti-tumoral activity and tumor-free survival was mediated by the co-administration of SAR T cells and BiAb in a syngeneic tumor model and was further confirmed in several xenograft models. Conclusions Here, we apply the SAR x BiAb approach in an effortto deliver specific and conditional activation of SAR transduced T cells, and targeted tumor cell lysis in melanoma models. The modularity of our approach is key for targeting melanoma and is essential towards personalised immunotherapies addressing cancer heterogeneity. Due to variations of antigen expression in primary melanoma tissues, we propose that a dual-targeting approach, either simultaneous or sequential, could mitigate issues of heterogeneity and deliver therapeutic benefit to patient
CRIS-Team WoS Importer:2022-12-23